TSUNAMI AND PALAEOTSUNAMI DEPOSITIONAL SIGNATURES AND THEIR POTENTIAL VALUE IN UNDERSTANDING THE LATE-HOLOCENE TSUNAMI RECORD - Dominey-Howes D.T.M.; Humphreys G.S.; Hesse P.P. (My University, 2006)
In recent years, much research on modern and palaeotsunami deposits has been published. From these studies, a range of signature types has been identified. Identifying and dating such deposits is an important element in understanding late-Holocene tsunami hazard and risk. However, important questions such as, 'do modern and palaeotsunami leave similar or dissimilar traces?'; 'do tsunami leave the same signatures all around the world or are there significant variations?'; and 'what is the actual record of tsunami in different parts of the world?' still remain. Answering these questions is not an easy task but examining megatsunami flood deposits should shed some light on these questions because such high-magnitude events should leave very clear and detailed traces within the coastal landscape. The coast of SE Australia is reported to have been affected by numerous palaeomegatsunami in the late Holocene. As such, the coast of New South Wales offers an important natural laboratory to examine in detail deposits associated with such events. Here, we summarize the published characteristics of modern and palaeotsunami deposits globally and within Australia. We briefly outline the tsunami risk to Australia before examining a site called Minnamurra Point on the coastline of SE Australia (south of Sydney) that has previously been described as containing evidence for a palaeomegatsunami of an unknown age. We describe the results of a detailed coastal survey, field stratigraphic investigation and various standard laboratory analyses. Surprisingly, we are unable to replicate the previously reported findings of tsunami deposits. Whilst we prefer the interpretation that the sequence is an in situ soil (the sediment sequence examined contains none of the usually reported lines of evidence to demonstrate tsunami provenance), we recognize and discuss the significance and difficulty of identifying tsunami deposits in the field and consider the implications of our findings to the wider debate about the preservation of tsunami-deposited sediments. © 2006 SAGE Publications.
Keywords: AUSTRALIA; EVIDENCE; HOLOCENE; PALAEOTSUNAMI; SIGNATURES; TSUNAMI; TSUNAMI RISK; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен